SIGNIFICANCE OF RAISING YOUTH'S LEGAL AWARENESS AND CULTURE IN THE SPIRITUAL EDUCATION PROCESS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Improving legal awareness and legal culture in society is one of the most important conditions for ensuring the rule of law and strengthening legality. Therefore, the Concept of Improving Legal Culture in Society was approved by the Decree of the President of the Republic of Uzbekistan No. PF-5618 “On Radical Improvement of the System for Improving Legal Awareness and Legal Culture in Society”, signed on January 9, 2019.